Etablierte Provisorien Leipzig und der lange Sommer der Migration - Schäfer, Philipp (Campus Verlag, 2022)
Using Leipzig as an example, Philipp Schäfer shows that the omnipresence of the provisional in the long summer of migration in 2015 was not the result of an abrupt crisis, but rather the result of longstanding disputes around questions of how to deal with refugees locally. Drawing on numerous interviews, observations and political documents, his sociological study demonstrates how the local governance of migration institutionalised provisionality and thus allowed refugees to be kept at a distance spatially, temporally and morally.